Integration of Science in Islamic Education to Develop Students' Multiple Intelligences - Wahyudin Wahyudin; Ruslan Ruslan; Ahmadin Ahmadin (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study aims to analyze the meaning of multiple competencies, the implementation of instruction, and the implications of science-based Islamic Religious Education at SMKN 1 Sanggar. The study employs a qualitative approach with data collection techniques including interviews, observations, and documentation, which were analyzed using data triangulation. The results of the study indicate that multiple competencies are understood as the holistic development of students’ abilities, encompassing spiritual, intellectual, and social aspects, as well as skills and critical thinking abilities. Instructional implementation is conducted contextually by integrating Islamic Religious Education content with natural phenomena, scientific advancements, daily life, and the professional world through methods such as discussion, case studies, and real-world examples. This approach enhances students’ engagement in the learning process. Furthermore, science-based Islamic Religious Education has positive implications for strengthening students’ multiple competencies, particularly in critical thinking, religious attitudes, responsibility, and the ability to connect Islamic values with real-life situations, thereby playing a relevant role in shaping students’ character and preparing them to face the challenges of the modern era.